Sexuality, communication and emotions: A situational study in women affected by gynecologic cancer - Pallí, Cristina; Lluch, Jun; Valero, Sergi (Psicooncología, 2010)
Gynaecological cancer and its treatment regimes profoundly affect several quality-of-life domains such as sexuality. Our study identifies main sexual symptoms and some factors related to sexual dysfunction. We interviewed women affected by ovarian, endometrial, cervical or vulvar cancer treated in our centre. Women answered a questionnaire on sociodemographic data, the Hospital Anxiety Depression Scale to evaluate emotional adjustment and the Woman Sexual Functioning Questionnaire to detect sexual symptoms. One third of all women (34%) had quitted sexual relations for cancer-related reasons. Sexually active women at the time of interview experienced the following symptoms: low lubrication (62.5%), low frequency of relations (57.8%) and poor sexual desire (57.8%); difficulties with excitation (62.5%), orgasm (39.1) and penetration (34.4%). Sexual functioning diminishes with depression (p=0.002) and anxiety. Longer time free of treatment tends to improve SF (p=0.045). No significant differences of SF were observed depending on cancer site, disease stage, age and menopause status. Gynaecologic cancer and its treatments profoundly affect sexuality. Most of women expressed their wish to be better informed. Further research should clarify the role of specific treatments.
Keywords: Sexuality; Gynaecological cancer; Sexual dysfunction